Investigation of the characteristics of electric heating carbon fiber fabric for infrared space heating systems - Філін, Дмитро Віталійович; Іванова, Віта Вікторівна (Eastern-European Journal of Enterprise Technologies, 2015)
The results of experimental studies of low-temperature electric heating carbon fiber fabric, used for space heating were presented in the paper. Flexible carbon fiber fabric is quick-response electric heating device, which consumes 242 W of power per running meter at a voltage of 48 V. The dependence of heating temperature on voltage in the range of 36 - 48 V is linear. Current-voltage characteristics, the dependence of the fiber fabric heating temperature and radiation spectrum on supply voltage were found, the temperature distribution throughout the fiber fabric at nominal voltage values was investigated using the thermal imager. It is shown that it is uniform. With the vertical fiber fabric fixing, temperature distribution unevenness is associated with convective cooling. The proposed method to determine the ratio between radiant and convective heat transfer component has allowed to estimate the radiation component in heat flow that goes for space heating as such that does not exceed 30% when fiber fabric heating to 50° – 60°С, which is essential, but does not allow to classify these low temperature heaters as solely IR heating elements. However, this does not exclude positive qualities of such systems, namely compactness, durability, easy installation on any surface and coverage. Research of alternating low-frequency electromagnetic field and current-voltage characteristic after the damage of CFF have proven the CFF safety.